Reviews. Issue 1 (1st May 2019) - Treagus, Mandy; Wright, Andrea; Sedgwick, Laura; Quanchi, Max; Leask, Rognvald; MacLean, Malcolm; Thode-Arora, Hilke; Quanchi, Max; Smith, Roy; Arnold, Katherine; Bryder, Linda; Albisson, Gregory; et al.
Gottfried Lindauer's New Zealand: The Māori Portraits, Ngahiraka Mason and Zara Stanhope (eds) (2016) Auckland: Auckland University Press, 284 pp., ISBN 978 1 86940 856 5 (hbk), NZ$75Strangers Arrive: Emigrés and the Arts in New Zealand, 1930–1980, Leonard Bell (2017) Auckland: Auckland University Press, 320 pp., ISBN 978 1 86940 873 2 (hbk), NZ$75Bloomsbury South: The Arts in Christchurch 1933–1953, Peter Simpson (2016) Auckland: Auckland University Press, 364 pp., ISBN 978 1 86940 848 0 (hbk), NZ$69.99Photographies calédoniennes d'antan: Des premiers contacts à la Grande guerre (1848–1918), Frédéric Angleviel (2017) Noumea: Pacific Footprint, 208 pp., ISBN 978 2 90816 620 0 (pbk), CFP 3900Working Lives c.1900: A Photographic Essay, Erik Olssen (2014) Dunedin: University of Otago Press, 176 pp., ISBN 978 1 87757 851 9 (pbk), NZ$50Dancing With the King: The Rise and Fall of the King Country, 1864–1885, Michael Belgrave (2017) Auckland: Auckland University Press, 452 pp., ISBN 978 1 86940 869 5 (hbk), NZ$65In Haste with Aloha: Letters and Diaries of Queen Emma, 1881–1885, David W. Forbes (ed.) (2017) Honolulu: University of Hawai'i Press, 256 pp., ISBN 978 0 82485 783 7 (pbk), US$45Conciliation on Colonial Frontiers: Conflict, Performance, and Commemoration in Australia and the Pacific Rim, Kate Darian-Smith and Penelope Edmonds (eds) (2015) Abingdon, Oxon: Routledge, 256 pp., ISBN 978 0 41574 430 0 (hbk), £120The Empires' Edge: Militarization, Resistance and Transcending Hegemony in the Pacific, Sasha Davis (2016) Athens, GA: University of Georgia Press, 176 pp., ISBN 978 0 82034 735 6 (pbk), USD$22.95Discovery and Empire: The French in the South Seas, John West-Sooby (ed.) (2013) Adelaide: University of Adelaide Press, 302 pp., ISBN 978 1 92206 453 0 (pbk), AU$55Doctors in Denial: The Forgotten Women in the 'Unfortunate Experiment', Ronald W. Jones (2017) Dunedin: Otago University Press, 248 pp., ISBN 978 0 94752 243 8 (pbk), NZ$39.95To the Mountains, a Collection of New Zealand Alpine Writings, Laurence Fearnley and Paul Hersey (eds) (2018) Dunedin: Otago University Press, 372 pp., ISBN 978 1 98853 120 5 (hbk), NZ$45Rugby: A New Zealand History, Ron Palenski (2015) Auckland: Auckland University Press, 462 pp., ISBN 978 1 86940 836 7 (pbk), NZ$69.99Good-Bye Maoriland: The Songs and Sounds of New Zealand's Great War, Chris Bourke (2017) Auckland: Auckland University Press, 308 pp., ISBN 978 1 86940 871 8 (pbk), NZ$59.99Hard Frost: Structures of Feeling in New Zealand Literature 1908–1945, John Newton (2017) Wellington: Victoria University Press, 368 pp., ISBN 978 1 77656 162 9 (pbk), NZ$40The Expatriate Myth: New Zealand Writers and the Colonial World, Helen Bones (2018) Dunedin: Otago University Press, 242 pp., ISBN 978 1 98853 117 5 (pbk), NZ$35Freelove, Sia Figiel (2016) Honolulu: Lō'ihi Press, 240 pp., ISBN 978 0 98225 355 7 (pbk), US$24.98